Effects of adaptogen supplementation on sport performance. A recent review of published studies - Molinos Domene, A. (Journal of Human Sport & Exercise, 2013)
Adaptogens are a new class of metabolic regulators (of a natural origin) which have been shown to increase the ability of organism to adapt to environmental factors and to avoid damage to the body from such factors. These properties make the possibility to use these substances to increase the performance in situations of mental and physical stress, and thus used it to improve in sport performance. Latest research show that Rhodiola rosea, Eleutherococcus senticosus, Schisandra Chinesis, Panax Ginseng and Erkang offer some benefits to use in sport nutrition.